Quality of Care for Hospitalized Children - Nacionales, Crissa Marie L. (JPAIR Multidisciplinary Research, 2008)
The study evaluated the existing services for hospitalized children at Davao Medical Center (DMC) and their alignment with international standards set by the United Nations Convention on the Rights of the Child (UNCRC). These guidelines emphasize a safe and caring environment, child-sensitive medical procedures, open communication among patients, families, and medical personnel, accessibility to developmental opportunities for children, and valuing children’s participation in their hospitalization. Using a descriptive research design, data were gathered through survey questionnaires based on the handbook Rights of the Hospitalized Child and focused group discussions. Respondents included 25% of pediatric inpatients during the survey period, with parents or guardians answering on behalf of children under six years old. Separate focus group discussions were held for pediatric patients and parents. The study also applied Donabedian’s quality dimensions focusing on structure and process. Findings revealed that while DMC provides satisfactory services, there is room for improvement in creating learning and play opportunities for hospitalized children. The study recommends that DMC collaborate with community partners, private sectors, and educational institutions offering courses in education, early childhood development, special education, and psychology to develop training programs. Additionally, incorporating an orientation on child life programs into hospital staff training could enhance service delivery. Strengthening partnerships with organizations like the Kythe Foundation could further improve services for hospitalized children, ensuring their rights are upheld and their hospital experience is more child-friendly.